Bitter roots - Crosby, Ellen, 1953- (Crosby, Ellen, 1953- Wine country mystery, 2022)
"In just over a week vineyard owner Lucie Montgomery and winemaker Quinn Santori will be married in a ceremony overlooking what should be acres of lush flowering grapevines. Instead they are confronted by an ugly swathe of slowly dying vines and a nursery owner who denies responsibility for selling the diseased plants. With neighboring vineyards facing the same problem, accusations fly and the ugly stand-off between supplier and growers looks set to escalate into open warfare. When Eve Kerr, a stunning blonde who works at the nursery, is found dead a few days later, everyone wonders if someone in the winemaking community went too far. What especially troubles Lucie is why Eve secretly arranged to meet Quinn on the day she was murdered - and whether Lucie's soon-to-be husband knows something he's not telling her. Then a catastrophic storm blows through, destroying everything in its path. With no power, no phones, and no wedding venue, Lucie needs to find out who killed Eve and what her death had to do with Quinn."--Amazon.